Patinkin, Perfect Competition, and Unemployment Disequilibria - Gogerty, D. Calvin; Winston, Gordon C. (Review of Economic Studies, 1964)
D. Calvin Gogerty, Gordon C. Winston; Patinkin, Perfect Competition, and Unemployment Disequilibria*, The Review of Economic Studies, Volume 31, Issue 2, 1 Apri